Informing primi and elderly pregnant women about iron sucrose administration for moderate anemia can improve treatment compliance in public health facilities, Kancheepuram health district, Tamil Nadu, India, 2017: A cross-sectional study - Anandan Mohan; Sakthivel Manikandanesan; Ponnaiah Manickam; Karumanagounder Kolandaswamy; Manoj Murhekar (Elsevier, 2021)
Introduction: Tamil Nadu administers intravenous iron sucrose for correcting moderate anaemia among pregnant women (Haemoglobin level 7-8.9 g/dl) based on preliminary studies. We did a cross-sectional study to estimate compliance level and that of factors associated with intravenous iron sucrose treatment for moderate anaemia among pregnant women attending health facilities of Kancheepuram health district, Tamil Nadu, India, 2017. Methods: We needed five pregnant women of 20-30 weeks from 70 clusters (health subcentres) for the assumptions of 64% compliance, 7% absolute precision, 95% Confidence Interval (CI) and a design effect of two. We collected data on knowledge and experience with iron sucrose treatment and reasons for non-compliance. We abstracted haemoglobin levels and administered doses from records. We computed compliance level (%) with 95% CI and estimated adjusted odds ratio (AOR) for non-compliance through logistic regression analysis. Results: The median age of 350 women was 24 years (Range = 22 to 26). Compliance level to intravenous iron sucrose was 79% (95% CI: 73 to 84). Non-compliance was more likely among women aged 25-35 years (AOR: 2.1, 95% CI: 1.2 to 3.7), primi (AOR: 2.2' 95% CI: 1.2 to 3.8) and not received treatment information (AOR: 3.1, 95% CI: 1.1 to 8.8). Major reasons for non-compliance were lack of information about treatment, belief that food was better than injections and that injections could harm the baby. Conclusions: The compliance to intravenous iron sucrose was insufficient. Providing clear information about intravenous iron sucrose to moderately anaemic pregnant women could increase the compliance to intravenous iron sucrose.